PENGARUH EDUKASI ONLINE BERBASIS FAMILY CENTERED MATERNITY CARE TERHADAP SELF EFFICACY IBU POSTPARTUM DALAM PEMBERIAN ASI EKSKLUSIF (JURNAL KESEHATAN MERCUSUAR, 2021)
The coverage of exclusive breastfeeding for infants aged 0-5 months in Indonesia in 2018 is only 37.3%. Self-efficacy is one of the main factors affecting the behavior of exclusive breastfeeding. During the Covid-19 pandemic, the self-efficacy of mothers for breastfeeding decreased, so increasing efforts are needed. Increasing knowledge can be done by providing online education based on family centered maternity care (FCMC). The purpose of this study was to determine the effect of FCMC-based online education on the self-efficacy of postpartum mothers in exclusive breastfeeding. This type of research is pre-experimental with one group pretest-posttest design with a total sample of 10 postpartum mothers. Data were analyzed using paired t-test. The results showed that the mean self-efficacy before being given online education was 41 with a standard deviation of 4.37, the mean self-efficacy after being given peer education was 59.8 with a standard deviation of 3.4. There is a difference in the mean value before and after the online education intervention was given with p-value = 0.000 (p